Nicholson’s Creation in World Scientific Research - Kholikov Zokhidjon Olimjonovich; Saliyev Yakubjan (Zien Journals, 2023)
Reynold Nicholson’s creation and translations have been studied by several scholars and researchers in world scientific research. They expressed positive and negative points about Nicholson’ translations.
Keywords: Arab; Persian; oriental; Sufism